Web-Based Education at Conventional Universities in China: A Case Study - Zhang, Weiyuan; Niu, Jian; Jiang, Guozhen (International Review of Research in Open and Distributed Learning, 2002)
With advances in information and communication technology (ICT), Web-based education has become an increasingly popular instructional mode all over the world. In recent years, the Chinese government has authorized a total of 45 universities to offer Web-based educational programs. One is China Central Radio and Television University, the Open University in China. The other 44 universities are all leading conventional universities. This case study is intended to provide a descriptive analysis of Web-based educational practices at the 44 leading conventional universities, by focusing on the current state of Web-based education in China and its discernible trends for the future. It is hoped this analysis of Web-based educational efforts in China will provide some insight for other countries.